Cannonball jellyfish digestion: an insight into the lipolytic enzymes of the digestive system - Raul B. Martínez-Pérez; Jorge A. Rodríguez; Luis Alonso Leyva Soto; Pablo Gortáres-Moroyoqui; Lourdes M. Diaz-Tenorio (PeerJ, 2020)
The digestive system and metabolism of the cannonball jellyfish Stomolophus sp. 2 are not well-known. The digestion study was critical to explain its ecology and bloom success. Different enzymes are involved in food digestion, which hydrolyze carbohydrates, proteins, and lipids. This study detected lipolytic activity in enzymatic extracts from gastric pouches of Stomolophus sp. 2 collected in the summer of 2013 at Bahía de Kino, Sonora, México (28°47′47″N 111°57′25″W). Lipase/esterase activity showed optimal pH at 11.0 and 50–60 °C with a half-life (t1/2) of 33 min at 55 °C, whereas halotolerance of this activity was recorded from 0-4 M NaCl. Metal ions Ca2+ and Mn2+ did not affect the activity, but Mg2+ decreased it 14.2% ± 3.15, while chelating agents as ethylenediaminetetraacetic acid reduced the activity 8.55% ± 2.13. Inhibition of lipase/esterase activity with tetrahydrolipstatin and paraoxon-ethyl decreased the activity 18.2% ± 2.3, and 62.80% ± 0.74, respectively, whereas phenylmethanesulfonyl fluoride (a protease inhibitor) did not affect it. The enzyme displayed a higher specificity for short-chain triglycerides, but triolein, coconut oil, olive oil, and fish oil were hydrolyzed. For the first time, phospholipase activity from the gastric pouch of Stomolophus sp. 2 was detected using L-α-phosphatidylethanolamine from chicken egg yolk as a substrate. These results suggest that Stomolophus sp. 2 hydrolyze several kinds of lipids, and lipolytic enzymes are active at alkaline pH under different saline conditions, which may be essential to digest different preys.